QBD Approach and Chemo metric Method Development for the estimation of Metoprolol succinate and Cilnidipine in combined solid dosage form - Dyade, G. K.; Jadhav, R. B.; Repal, Sanket; Uparwad, Shital; Suryawanshi, Prashant; Taware, Aashish; Khapne, Sonali; Kokare, Shweta; Dnyaneshwar, Anuse (Indian Journal of Pharmacy & Drug Studies, 2024)
Background: Development of several pharmaceutical processes including analytical methods by applying Quality by design assists in ensuring the robustness of the method. USFDA and other regulatory agencies have recommended implementation of Quality by design (QbD) a systematic process for pharmaceutical development along with its significance. Objective: Chemo metric assisted UV-VIS spectrophotometric analytical method based on QbD was developed for the estimation of metoprolol succinate (MET) and cilnidipine (CIL) from the combined dosage forms. Method: Nature of spectra focused applicability of absorbance correction and amplitude modulation methods for estimation of both drugs from the formulations; and 50 % alcohol was being the common solvent. For both this method 221 nm and 242 nm was the wavelength for measurement of absorbance of metoprolol and cilnidipine respectively. Effect of input variables on spectrum characteristics were studied for selection of critical parameters and developed method was validated as per ICH Q 2 R1 regulatory guidelines. Result and conclusion: Linearity of the drugs was ascertained over the conc range 1-36 μg/ml (microgram/ml) for MET and 1-16 μg/ml for CIL. The percentage purity of assay in method II was found 103.773 % for MET and 96.825 % for CIL; and the accuracy study data of method I were varied 2.04859 for MET and 1.26321 for CIL. Precision study was shown acceptable data as % RSD in method I data varied 0.58894 for MET and 1.15116 for CIL. The developed method is rigid, robust and efficient for the estimation of MET and CIL from the composition of dosage form.